Analysis of Savings and Loan Practices of Women's Groups of National Madani Capital Mekar Syariah at the Bengkalis Branch Office in a Review of Islamic Economics - Surohman, Irzan; Azlina, Nur; Indira, Nur; Listiawati, Irda; Rini, Disti Marta; Hasan, Zulfikar (Westscience Press, 2023)
The purpose of this research is to find out how savings and loan practices are carried out at Civil National Capital. This type of research is field research conducted to explore data obtained from the location or research field. This research is classified as a qualitative research using a qualitative descriptive approach. The population in this study were members of national civil capital customers and the sampling technique was purposive sampling with certain criteria in selecting the sample to achieve the research objectives. The research was made up of 10 members of the Gg Kundur women's group. The results of the study show that with this loan the customer is greatly assisted in running his business.